BANK SAMPAH SEBAGAI ALTERNATIF STRATEGI PENGELOLAAN SAMPAH BERBASIS MASYARAKAT DI SONGOWARENGI - Bilgies, Ana Fitriyatul; Zulkarnaen, Have; Fauziyah, Nurul; Sulistyowati, Anjar; Rozi, Ahmad Fathur (Journal of Social Comunity Services, 2024)
A change in the paradigm of society regarding waste needs to be carried out in a sustainable manner. Education of residents' awareness and skills for waste management with the application of the principles of reduce, reuse, recycle and replant (4R) is important in solving waste problems through waste management from the source. Waste banks are one of the effective strategies to overcome waste management problems in rural areas. Waste bank activities are the concept of collecting dry waste and sorting and have management like banking but what is saved is not money but waste. In operating a waste bank, active community participation is essential. Empowering citizens through counseling, education, training activities with emancipatory participation methods (interaction and communication), as well as dialogue with residents in the community. Residents Waste bank managers with related stakeholders. The Waste Bank in Songowareng village has provided benefits to residents, especially direct benefits by reducing waste generation in the community, a cleaner and more beautiful environment, and economic independence of residents.